A Qualitative Course-Based Inquiry into Child and Youth Care Students’ Insights Concerning the Theoretical Frameworks that Guide their Efforts to Form Meaningful Connections with Children, Youth, and Families - Jadyn Adams; Shaelyn Korpach; Payton O’Keefe; Cheyanne Soetaert; Gerard Bellefeuille (Randwick International of Social Science Journal, 2022)
The purpose of this course-based inquiry was to gain insight into how child and youth care (CYC) students apply theoretical frameworks in their connection-building efforts with children and youth. A qualitative research design was chosen for the purpose of capturing the lived experiences of the CYC student participants. The findings presented in this study revealed three overarching themes: a) provides pathways of understanding, b) all about building trust, and c) feeling understood and accepted.